Quantum coherence effects in a Raman amplifier - Ooi, Chong Heng Raymond; Ahmad, Harith; Harun, Sulaiman Wadi (Taylor & Francis, 2011)
We have studied optical pulse propagation in a Raman fiber amplifier doped with a three-level medium and driven by a control laser pulse. We analyze the spatial-temporal dynamics of pulse propagation for different atomic initial conditions. The propagation of an optical pulse through the amplifier can be sustained by a control laser that induces transparency via quantum coherence, which is useful for extending the distance between optical repeaters. Under certain conditions, amplification is achieved without population inversion. The results could be useful for laser control of optical pulses in amplifiers and waveguides.